Pengembangan Layanan Bimbingan Klasikal Berbantuan Media Inovatif untuk Mengurangi Perilaku Bullying di SMK Wira Harapan Tahun 2026 - Adrina Yunindaliony Putri; Ni Komang Sri Yuliastini; I Nyoman Rajeg Mulyawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study was conducted to develop a classical guidance service supported by innovative media as an effort to address bullying behavior among students at SMK Wira Harapan in 2026. Bullying remains a significant issue in schools, as it can adversely affect students’ psychological well-being, social relationships, and academic performance. Therefore, there is a need for guidance services that are more engaging, interactive, and responsive to students’ needs. This research employed the Research and Development (R&D) approach using the Plomp development model, which consists of three phases: preliminary research, prototyping, and assessment. The participants involved in this study included material experts, media experts, and students. Data were gathered through expert validation sheets and student response questionnaires based on a four-point Likert scale. The findings revealed that the developed product achieved a very high level of feasibility according to expert evaluations and received favorable responses from students. These results indicate that the innovative media developed in this study is appropriate for supporting the implementation of classical guidance services and has the potential to serve as an alternative medium for promoting bullying prevention efforts in schools.